2014
DOI: 10.5312/wjo.v5.i4.550
|View full text |Cite
|
Sign up to set email alerts
|

Donor’s site evaluation after restoration with autografts or synthetic plugs in rabbits

Abstract: AIM:To investigate donor site's area histological and immunohistochemical knee cartilage appearances after resurfacing iatrogenic defects with biosynthetic plugs orautografts. METHODS:Thirty New Zealand White rabbits were used in this study. A full-thickness cylindrical defect of 4.5 mm (diameter) × 7 mm (depth) was created with a hand drill in the femoral groove of every animal. In Group A (n = 10) the defect of the donor site was repaired with a biosynthetic osteochondral plug, in Group B (n = 10) with an os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Bartha et al 1 filled the donor sites with artificial materials to reduce donor site morbidity and postoperative bleeding after mosaicplasty. Using a rabbit model, Intzoglou et al 12 reported that the donor site area was better revised with osteochondral graft than with a bone graft substitute implant. In the present study, the donor defects were filled to the level of the subchondral bone with bone chips from the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…Bartha et al 1 filled the donor sites with artificial materials to reduce donor site morbidity and postoperative bleeding after mosaicplasty. Using a rabbit model, Intzoglou et al 12 reported that the donor site area was better revised with osteochondral graft than with a bone graft substitute implant. In the present study, the donor defects were filled to the level of the subchondral bone with bone chips from the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, osteochondral autologous transfer is the most attractive surgical technique. However, it confers undesirable postoperative pain in the donor area [18].…”
Section: Introductionmentioning
confidence: 99%